Ibn Khaldun dan Pemikir Sosial Budaya - Zainuddin, M. (UIN Maulana Malik Ibrahim Malang, 2000)
The greatness of Ibn Khaldun's name makes the world recognized and reviewed his thoughts. If we revisit the treasury of medieval Islamic intellectual thought and develop a tradition of thought in the world of campus, this tradition and culture is good to do. This paper raises who is really the figure of Ibn Khaldun and how his thoughts are especially on his social cultural thinking. Ibn Khaldun's theory of social phenomena includes the theory of evolution that views social phenomena as the dynamics of society, nations and states that differ across generations. The human society according to Ibn Khaldun is an independent entity. and can be perfectly managed regardless of religious values. He says humans can be good and evil at the same time. Man is evil because of animal nature, and on the contrary, man is good because of his involvement with other human beings. Ibn Khaldun's mind is so visionary that it is relevant to the context of the development of the era as developed by modern philosophers which actually comes from the socio-cultural view of Ibn Khaldun. Begitu besar nama Ibn Khaldun sehingga dunia mengakui dan mengkaji kembali pemikiran-pemikirannya. Jika kita menguak kembali khazanah pemikiran intelektual Islam abad pertengahan dan mengembangkan tradisi pemikiran di dunia kampus, tradisi dan budaya ini bagus untuk dilakukan. Tulisan ini mengangkat siapakah sesungguhnya sosok Ibn Khaldun itu dan bagaimana pemikirannya khususnya pada pemikiran sosial budayanya. Teori fenomena sosial Ibn Khaldun termasuk teori evolusi yang memandang fenomena sosial sebagai dinamika masyarakat, bangsa dan negara yang berbeda antar generasi. Masyarakat manusia menurut Ibn Khaldun adalah suatu entitas yang independen. dan dapat diurus secara sempurna lepas dari nilai-nilai agama. Menurutnya manusia bisa baik clan jahat pada saat yang sama. Manusia jahat karena adanya sifat dasar kebinatangan, dan sebaliknya, manusia itu baik karena keterlibatannya dengan manusia lain. Pemikiran Ibn Khaldun sangat visioner sehingga relevan dengan konteks perkembangan jaman sebagaimana yang kemudian dikembangkan oleh filsuf modern yang sesungguhnya bermuara dari pandangan sosial budaya Ibnu Khaldun.